1996
DOI: 10.1055/s-0038-1650217
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Monoclonal Antibody Purified Factor IX Concentrate in Previously Untreated Patients with Hemophilia B

Abstract: SummaryThe safety and efficacy of a monoclonal antibody purified factor IX concentrate were evaluated in two continuing trials of 32 previously untreated patients with mild, moderate, or severe hemophilia B. Patients were evaluated every 2 weeks for 24 weeks and every 3 months thereafter for at least 1 year. No patients became positive for human immunodeficiency virus antibody or hepatitis C virus antibody during the trial. Two patients developed a false-positive hepatitis B core antibody, one transiently, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 0 publications
4
23
0
Order By: Relevance
“…5,[28][29][30] The development of inhibitors occurs in 1% to 3% of patients with hemophilia B, 29 but may be higher in individuals with severe disease. 29,31 In the current study, the incidence of FIX inhibitor was 2 of 63 (3%) patients, which is consistent with previous reports of hemophilia B patients treated with pdFIX products 9,32 or PTPs treated with rFIX. 20 Inhibitory antibodies occur most frequently in hemophilia B patients with major derangements of the F9 gene, due to large deletions, stop codons, and frame shift mutations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…5,[28][29][30] The development of inhibitors occurs in 1% to 3% of patients with hemophilia B, 29 but may be higher in individuals with severe disease. 29,31 In the current study, the incidence of FIX inhibitor was 2 of 63 (3%) patients, which is consistent with previous reports of hemophilia B patients treated with pdFIX products 9,32 or PTPs treated with rFIX. 20 Inhibitory antibodies occur most frequently in hemophilia B patients with major derangements of the F9 gene, due to large deletions, stop codons, and frame shift mutations.…”
Section: Discussionsupporting
confidence: 92%
“…Most responses to rFIX routine prophylaxis were rated "excellent" (91%), indicating that prophylaxis treatment during the preceding 3 months completely prevented spontaneous musculoskeletal bleeding episodes and that no change in rFIX regimen was necessary. These responses to rFIX for on-demand and prophylactic treatment regimens are similar to those reported in other studies of pdFIX in patients with hemophilia B 9,[23][24][25][26] and for rFIX in PTPs. 20 In the current study, the incidence of AEs related to rFIX treatment was low, occurring in 17% of patients, with most related AEs reported as mild or moderate in severity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although this was not a comparative study, hemostatic efficacy of rFIX was rated against participants' previous experience with pdFIX in "ondemand" and "secondary prophylaxis" regimens, and was reported as "excellent" or "good" in 90.9% to 98% of bleeding episodes, consistent with those reported in other studies that evaluated pdFIX in individuals with hemophilia B. [25][26][27][28][29][30] In addition, an analogous study testing rFVIII in PTPs with hemophilia A reported hemostatic efficacy as "excellent" or "good" in 91.2% of bleeding episodes, 31 similar to our results with rFIX in PTPs with hemophilia B.…”
Section: Discussionmentioning
confidence: 62%
“…6,[18][19][20][21] A recently approved long-acting FIX product, rFIXFc, demonstrated a terminal half-life of 82.1 hours when patients were dosed 50 IU/kg once weekly, whereas the steady state half-life of nonacog beta pegol was between 107 and 111 hours. 21 However, key differences between the trials for rFIXFc and nonacog beta pegol, namely prophylaxis regimes, dose adjustments, and pharmacokinetic analysis, make direct comparisons between these products difficult.…”
Section: Org Frommentioning
confidence: 99%